2012
DOI: 10.1002/jssc.201200231
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of fucoxanthin from edible brown algae by microwave‐assisted extraction coupled with high‐speed countercurrent chromatography

Abstract: A rapid and efficient method for the separation and purification of fucoxanthin from edible brown algae by microwave-assisted extraction coupled with high-speed countercurrent chromatography was developed. The algae were first extracted using microwave-assisted extraction, then the dried extract was dissolved and directly introduced into the high-speed countercurrent chromatography system with a two-phase solvent system consisting of hexane-ethyl acetate-ethanol-water (5:5:6:4, v/v/v/v). The isolation was done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(69 citation statements)
references
References 22 publications
2
67
0
Order By: Relevance
“…It has been reported to induce apoptosis in several human cancer cell lines such as PC-3 [12], colon cancer Caco-2 [13], and leukemia HL-60 cells [14] through down-regulating Bcl-2 expression. In addition, fucoxanthin was found to inhibit the growth of tumor cells (hepatic carcinoma HepG2, colon adenocarcinoma WiDr, prostate cancer DU145 and leukemia cancer HL-60 cells), induce cell cycle arrest at the G 1 phase by cyclin D, p21WAF1/Cip1, and MAPK regulation, and inactivate the Bcl-xl pathway by the generation of reactive oxygen species (ROS), respectively [15][16][17]. Our previous research indicated that fucoxanthin can induce the apoptosis of human bladder cancer EJ-1 cells [18], which was identified to be the same cell line as T24 cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported to induce apoptosis in several human cancer cell lines such as PC-3 [12], colon cancer Caco-2 [13], and leukemia HL-60 cells [14] through down-regulating Bcl-2 expression. In addition, fucoxanthin was found to inhibit the growth of tumor cells (hepatic carcinoma HepG2, colon adenocarcinoma WiDr, prostate cancer DU145 and leukemia cancer HL-60 cells), induce cell cycle arrest at the G 1 phase by cyclin D, p21WAF1/Cip1, and MAPK regulation, and inactivate the Bcl-xl pathway by the generation of reactive oxygen species (ROS), respectively [15][16][17]. Our previous research indicated that fucoxanthin can induce the apoptosis of human bladder cancer EJ-1 cells [18], which was identified to be the same cell line as T24 cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…In this technology, parameters such as the selection of the two-phase solvent system, the elution mode, flow rate, and rotation speed are manipulated in order to obtain higher purification of the product of interest [54]. Some studies have reported the use of HSCCC technology for astaxanthin [39], fucoxanthin [38], lutein and zeaxanthin purification [40,41] (Tab. 2).…”
Section: Low Robustness Techniques With High Resolutionmentioning
confidence: 99%
“…HSCCC technology is another type of liquid-liquid partition chromatography based on hydrodynamic principles [38] that is widely used in the preparative isolation of natural products. This technique is preferred due to its larger separation capacity than HPLC and the possibility to process crude extracts [41].…”
Section: Low Robustness Techniques With High Resolutionmentioning
confidence: 99%
“…SCO 2 provided the highest purity of Fucoxanthin (0.151 mg FE/mg extract) and also the highest purity of Xanthophyll (0.008 mg XE/mg extract). Xiao et al, (2012) isolated fucoxanthin from edible brown algae by microwave assisted extraction coupled with high speed countercurrent chromatography and investigated the purity of each fucoxanthin fraction. They found the…”
Section: Analysis Of Fucoxanthin and Xanthophyll Content Using Differmentioning
confidence: 99%